Misbehavior or misalignment? Examining the drift towards bureaucratic box-ticking in Competency-Based Medical Education. - Alicia C Strand; Andrea Gingerich; Vijay John Daniels (PLoS ONE)
Within competency-based medical education (CBME) residency programs, Entrustable Professional Activity (EPA) assessments endeavor to both bolster learning and inform promotion decisions. Recent implementation studies describe successes but also adverse effects, including residents and preceptors drifting towards bureaucratic / purely administrative behaviors and attitudes, although the drivers behind this tendency are not adequately understood. This study sought to examine resident and faculty experiences with implemented EPA processes to elucidate what leads them toward a 'tick-box' approach that has been described in the literature. The internal medicine residency program at the University of Alberta implemented a CBME pilot in 2016. From March to June 2018, a research assistant interviewed 16 residents and 27 preceptors shortly after they completed an EPA assessment. They described their goals, judgements, and actions during a recent EPA observation. Three researchers analyzed the data to identify themes following qualitative description methodology. The requirement to accrue EPA assessments turned them into currency exchanged by preceptors and residents to acknowledge clinical work. Predicaments arose when the prescriptive EPA process felt misaligned with the assessment context. The selected encounter sometimes suited formative but not summative purposes. Preceptors variably prioritized the dual formative and summative purposes and framed the message for either the resident's or the program's benefit. The drift toward bureaucracy in workplace-based assessments is becoming a predictable implementation pattern. Instead of solely attributing this pattern to residents and preceptors misusing the assessment process, viewing their actions as workarounds suggests that users make rational choices to overcome obstacles in the assessment system. Obstacles identified by workarounds could be targeted by design modifications.